2012
DOI: 10.3113/fai.2012.0057
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness and Validity of the SF-36, Ankle Osteoarthritis Scale, AOFAS Ankle Hindfoot Score, and Foot Function Index in End Stage Ankle Arthritis

Abstract: Background: We examined four commonly used scores, the SF-36, the Ankle Osteoarthritis Scale (AOS), the American Orthopaedic Foot and Ankle Society (AOFAS) Ankle Hindfoot Score, and the Foot Function Index (FFI) to determine their responsiveness and validity. Methods: Patients with end stage ankle arthritis were recruited into a prospective multicenter cohort study and baseline and one year outcome scores were compared. The Standardized Response Mean and Effect Size for the AOS, AOFAS, and FFI were calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
163
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(176 citation statements)
references
References 26 publications
6
163
2
5
Order By: Relevance
“…The present literature describes 36 different PROMs used to measure foot problems in RA patients; solely five instruments were measured for responsiveness [9]. A worldwide (USA, Europe, Australia and Asia) used PROM to measure the impact of foot pathology on function in terms of pain, difficulty and activity restriction is the Foot Function Index [10,11] as described by Budiman et al Nelson et al reported moderate to large responsiveness of the FFI in RA patients receiving foot or ankle surgery; however, they did not specify the operative procedure [12]. The responsiveness of the FFI in end stage ankle arthritis patients, who received either a total ankle replacement or an ankle arthrodesis, showed a high level of responsiveness (both the standardized effect size and standardized response mean above the threshold of 0.8 indicating a high level of responsiveness) [13].…”
Section: Introductionmentioning
confidence: 99%
“…The present literature describes 36 different PROMs used to measure foot problems in RA patients; solely five instruments were measured for responsiveness [9]. A worldwide (USA, Europe, Australia and Asia) used PROM to measure the impact of foot pathology on function in terms of pain, difficulty and activity restriction is the Foot Function Index [10,11] as described by Budiman et al Nelson et al reported moderate to large responsiveness of the FFI in RA patients receiving foot or ankle surgery; however, they did not specify the operative procedure [12]. The responsiveness of the FFI in end stage ankle arthritis patients, who received either a total ankle replacement or an ankle arthrodesis, showed a high level of responsiveness (both the standardized effect size and standardized response mean above the threshold of 0.8 indicating a high level of responsiveness) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the data obtained with these questions might not accurately represent the patient's status, because the physician's expectations could influence the data. Third, if the physician completing these objective elements has not been properly trained, the reliability of the results could be threatened (14). In contrast, the AFAQ consists entirely of questions related to subjective discomfort; thus, it is advantageous regarding the procurement of data that effectively measures the patient's status.…”
Section: Discussionmentioning
confidence: 98%
“…The AOFAS scale studies reported the scales could evaluate the outcomes of surgery (12), and their subjective component had acceptable validity (13). However, other studies have reported that the AOFAS scales are difficult to perform and lack reliability (14), validity, and precision (15)(16)(17).…”
mentioning
confidence: 98%
“…The AOFAS scale includes both subjective and objective methods of evaluation and has been shown to be a valuable tool in assessing pre-and postoperative ankle function. Madeley et al (27) compared several commonly used scoring systems, including the AOFAS scale, the Medical Outcomes Study short-form 36-item questionnaire, the AOS, and the foot function index, and found all 4 scores to be a valid method of assessment. However, the objective portion of the AOFAS has not been shown to be reliable and can often be difficult to perform on patients with severe ankle arthritis.…”
Section: Discussionmentioning
confidence: 99%